1997
DOI: 10.1161/01.cir.95.8.2032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of 5,10-Methylenetetrahydrofolate Reductase (MTHFR) as a Risk Factor for Coronary Artery Disease

Abstract: The VV genotype of MTHFR was also common in the Japanese population and was significantly associated with CAD. The frequency of this genotype in particular was correlated with the severity of disease. The VV genotype associated with a predisposition to increased plasma homocyst(e)ine levels may represent a genetic risk factor for CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
183
7
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(211 citation statements)
references
References 31 publications
20
183
7
1
Order By: Relevance
“…With respect to MTHFR gene polymorphism, 136 had genotype CC, 136 genotype CT, and 54 genotype TT. The distribution of MTHFR genotypes was consistent with published data for Japanese subjects (Morita et al 1997) and was in agreement with the expected Hardy-Weinberg ratio (P ϭ 0.36). Among the three MTHFR genotypes, there were no differences in background factors, including age, history of cigarette smoking, blood pressure, lipids, and uric acid, or in the incidence of atherosclerotic diseases such as hypertension, diabetes mellitus, ischemic heart disease, or cerebral infarction (Table 1).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…With respect to MTHFR gene polymorphism, 136 had genotype CC, 136 genotype CT, and 54 genotype TT. The distribution of MTHFR genotypes was consistent with published data for Japanese subjects (Morita et al 1997) and was in agreement with the expected Hardy-Weinberg ratio (P ϭ 0.36). Among the three MTHFR genotypes, there were no differences in background factors, including age, history of cigarette smoking, blood pressure, lipids, and uric acid, or in the incidence of atherosclerotic diseases such as hypertension, diabetes mellitus, ischemic heart disease, or cerebral infarction (Table 1).…”
Section: Resultssupporting
confidence: 90%
“…There have been numerous genetic association studies of the MTHFR C677T variant, particularly in the homozygous state, which have shown both the presence (Arruda et al 1997;Cattaneo et al 1997;Christensen et al 1997;Kluijtmans et al 1997;Morita et al 1997) and absence (Anderson et al 1997;Legnani et al 1997;Ma et al 1996;Press et al 1999;Rees et al 1997;Schwartz et al 1997) of significant associations with such end points as coronary heart disease, myocardial infarction, thrombo-occlusive disease, and cerebrovascular disease. However, the relationship between elevated plasma Hcy concentration and the end points of vascular disease appears to be consistent, even in those studies that failed to show an association with the MTHFR C677T variant.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of increased risk for cardiovascular disease in persons with the MTHFR C677T mutation (Morita et al 1997;Kang et al 1988Kang et al , 1991Gallagher et al 1996;Kluijtmans et al 1996). In one study, the presence of the MTHFR C677T mutation in a group of patients with venous thromboembolic disease in various parts of the body, mainly in deep large veins was examined (Arruda et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigations have been done to identify whether the thermolabile mutant, MTHFR C677T causes an increased risk for cardiovascular disease. Some results suggest such a correlation (Morita et al 1997;Kang et al 1988Kang et al , 1991Gallagher et al 1996;Kluijtmans et al 1996), whereas others do not (Verhoef et al 1997;Anderson et al 1997;Ma et al 1996;Deloughery et al 1996;van Bockxmeer et al 1997;Christensen et al 1997;Wilcken et al 1996;Adams et al 1996;Brugada & Marian;1997). Arruda et al have shown that there is a correlation between homozygosity for the MTHFR C677T mutation and venous thromboembolic disease (Arruda et al 1997).…”
mentioning
confidence: 99%
“…TT MTHFR homozygotes are predisposed to increased plasma homocysteine levels, particularly in individuals with low folate [22,23]. Hyperhomocysteinemia has been implicated in premature vascular disease [24], venous thrombosis [25] and unexplained early pregnancy loss [23,26]. Hyperhomocysteinemia caused by the C677T polymorphism has been associated with coronary artery disease, venous thrombosis and complications of pregnancy i.e.…”
Section: Introductionmentioning
confidence: 99%